Plan Tissue Culture Engineering - Gupta, S. Dutta; Ibaraki, Yasuomi; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
It is my privilege to contribute the foreword for this unique volume entitled: (3z(BPlant Tissue Culture Engineering,(3y (Bedited by S. Dutta Gupta and Y. Ibaraki. While there have been a number of volumes published regarding the basic methods and applications of plant tissue and cell culture technologies, and even considerable attention provided to bioreactor design, relatively little attention has been afforded to the engineering principles that have emerged as critical contributions to the commercial applications of plant biotechnologies. This volume, (3z(BPlant Tissue Culture Engineering,(3y (Bsignals a turning point: the recognition that this specialized field of plant science must be integrated with engineering principles in order to develop efficient, cost effective, and large scale applications of these technologies. I am most impressed with the organization of this volume, and the extensive list of chapters contributed by expert authors from around the world who are leading the emergence of this interdisciplinary enterprise. The editors are to be commended for their skilful crafting of this important volume. The first two parts provide the basic information that is relevant to the field as a whole, the following two parts elaborate on these principles, and the last part elaborates on specific technologies or applications.s
Machine Vision -- Evaluation of photosynthetic capacity in micropropagated plants by image analysis -- Monitoring Gene Expression In Plant Tissues -- Applications And Potentials Of Artificial Neural Networks In Plant Tissue Culture -- Evaluation Of Plant Suspension Cultures By Texture Analysis -- BioReactor Technology -- Bioengineering Aspects Of Bioreactor Application In Plant Propagation -- Agitated, Thin-Films Of Liquid Media For Efficient Micropropagation -- Design, Development, And Applications Of Mist Bioreactors For Micropropagation And Hairy Root Culture -- Bioreactor Engineering For Recombinant Protein Production Using Plant Cell Suspension Culture -- Types And Designs Of Bioreactors For Hairy Root Culture -- Oxygen Transport In Plant Tissue Culture Systems -- Temporary Immersion Bioreactor -- Design And Use Of The Wave Bioreactor For Plant Cell Culture -- Mechanized Micropropagation -- Integrating Automation Technologies With Commercial Micropropagation -- Machine Vision And Robotics For The Separation And Regeneration Of Plant Tissue Cultures -- Engineering Cultural Environment -- Closed Systems For High Quality Transplants Using Minimum Resources -- Aeration In Plant Tissue Culture -- Tissue Culture Gel Firmness: Measurement And Effects On Growth -- Effects Of Dissolved Oxygen Concentration On Somatic Embryogenesis -- A Commercialized Photoautotrophic Micropropagation System -- Intelligent Inverse Analysis For Temperature Distribution In A Plant Culture Vessel -- Physical Aspects Of Plant Tissue Engineering -- Electrical Control Of Plant Morphogenesis -- The Uses Of Ultrasound In Plant Tissue Culture -- Acoustic Characteristics Of Plant Leaves Using Ultrasonic Transmission Waves -- Physical And Engineering Perspectives Of In Vitro Plant Cryopreservation.
Keywords: Life sciences; Cell biology; Bioinformatics; Computational biology; Developmental biology; Plant science; Botany; Plant anatomy; Plant development; Plant pathology; Life Sciences; Plant Sciences; Cell Biology; Computer Appl. in Life Sciences; Developmental Biology; Plant Anatomy/Development.; Plant Pathology; Electronic books